Diagnostic and prognostic potential of exosome non-coding RNAs in bladder cancer: a systematic review and meta-analysis - Chen, Yani; Shi, Kesong; Fu, Xinyao; Guo, Hua; Gao, Tian; Yu, Haiquan (Frontiers in Oncology, 2024)
Background Bladder cancer stands as the predominant malignant tumor in the urological system, presenting a significant challenge to public health and garnering extensive attention. Recently, with the deepening research into tumor molecular mechanisms, non-coding RNAs (ncRNAs) have emerged as potential biomarkers offering guidance for the diagnosis and prognosis of bladder cancer. However, the definitive role of ncRNAs in bladder cancer remains unclear. Hence, this study aims to elucidate the relevance and significance of ncRNAs through a Meta-analysis. Methods A systematic meta-analysis was executed, including studies evaluating the diagnostic performance of ncRNAs and their associations with overall survival (OS) and diseasefree survival (DFS). Key metrics such as hazard ratios, sensitivity, specificity, and diagnostic odds ratios were extracted and pooled from these studies. Potential publication bias was assessed using Deeks' funnel plot, and the robustness of the results was ascertained through a sensitivity analysis. Results Elevated ncRNA expression showed a positive correlation with improved OS, evidenced by a hazard ratio (HR) of 0.82 (95% CI: 0.66-0.96, P<0.001). Similarly, a significant association was observed between heightened ncRNA expression and DFS, with an HR of 0.86 (95% CI: 0.73-0.99, P<0.001). Diagnostic performance analysis across 17 articles yielded a pooled sensitivity of 0.76 and a specificity of 0.83. The diagnostic odds ratio was recorded at 2.71, with the area under the ROC curve (AUC) standing at 0.85. Conclusion Exosome ncRNAs appear to possess potential significance in the diagnostic and prognostic discussions of bladder cancer. Their relationship with survival outcomes and diagnostic measures suggests a possible clinical utility. Comprehensive investigations are needed to fully determine their role in the ever-evolving landscape of bladder cancer management, especially within the framework of personalized medicine.